Using hedges as relational work by Arab EFL students in student-supervisor consultations - Ahmed, Wasan Khalid; Marlyna Maros, (Penerbit Universiti Kebangsaan Malaysia, 2017)
One of the challenges that Arab EFL male and female postgraduate students in the Malaysian universities have to anticipate is the consultation process with their supervisors regarding their academic projects. During the consultations, the students ask questions and respond to the supervisors’ comments and demands. To perform these academic tasks appropriately, these students need to modify their interactional patterns using various linguistic devices. One of these is hedges, the linguistic politeness markers. Incorrect selection of these devices can be interpreted as inappropriate behaviour, which may affect the student-supervisor relationships. To avoid any breakdown in communication between the two parties and maintain effective consultations, a pragmatic knowledge of using hedges is necessary. Previous discourse analysis studies on the use of hedges have focused on the student-student interaction while student-supervisor academic consultations still need to be explored to understand how these learners perform in more formal academic settings. The current study, therefore, aimed to investigate how Arab EFL postgraduate students use hedges to express various types of politeness. It also aimed to find out whether the use of this device is gender specific. The data were collected by means of four one-to-one student-supervisor consultations and a pragmatic knowledge questionnaire. The findings showed that the students are familiar with hedges as they used a huge number of them. Also the female students used more hedges than male students. However, the analysis of the questionnaire showed that the students were not fully aware of the pragmatic functions achieved by these devices.